THE INFLUENCE OF HEALTH EDUCATION ON MASSAGE FOR BABIES AGED 3-6 MONTH ON MOTHERS' ATTITUDES AT POSYANDU DELIMA - Harahap, Lenni Ana; Futriani, Elfira Sri (HEARTY, 2025)
Background: according to data from the World Health Organization (WHO), 200 million children aged under 5 years in the world do not fulfill their developmental potential. The incidence of stunting in Australia is 3.4%, Japan 5%, Saudi Arabia 12.4%, Malaysia 21.9%, and Indonesia 31%. Based on the results of interviews, it was found that there was still a high negative attitude of mothers towards massage for babies aged 3-6 months at Posyandu Delima, Jatiluhur Village, Jatiasih District, Bekasi City. The aim of this research is to determine the effect of Health Education regarding massage for babies aged 3-6 months on the attitudes of mothers at Posyandu Delima, Jatiluhur Village, Jatiasih District, Bekasi City. Specific objectives identifying maternal characteristics based on age, education, occupation, whether or not they received information and sources of information, attitudes before and after being given Health Education, analyzing the influence of Health Education on maternal attitudes. This research method uses a pre-experimental method with a one group pretest-posttest design. The sample for this research was 60 ressspondents using purposive sampling. Data collection techniques include editing, coding, processing, cleaning and tabulating. Data processing uses the help of the IBM SPSS Statistics 22.0 for Windows 10 program. The research results showed that of the 52 respondents before being given Health Education about massage for babies aged 3-6 months, almost all of them had a negative attitude, 41 respondents (78.8%), and after being given Health Education, the majority of respondents had a positive attitude, 34 respondents (65.4%). %). The results of the Mc Nemar Statistical Test obtained a significant number (r value=0.000) which was lower than the standard value (a=0.05) or r < a. The conclusion in writing this research is that there is an influence of Health Education regarding massage for babies aged 3-6 months on the attitude of mothers at Posyandu Delima, Jatiluhur Village, Jatiasih District, Bekasi City.